Effective Utilization of Fast-Growing Acacia mangium Willd. Timber As a Structural Material - Anita Firmanti; Kohei Komatsu; Suichi Kawai (Jurnal Ilmu dan Teknologi Kayu Tropis, 2007)
This study aims to evaluate the full-scale strength performance of Acacia mangium Willd. timber and establish characteristic values, as well as the timber strength classes, by the application of mechanical grading. A total of 120 actual size specimens were selected from two areas and the modulus of elasticity and modulus of rupture were tested. The results showed that A. mangium timber could be a substitute structural material for light timber construction. Effective utilization of A. mangium timber could be obtained when the timber is mechanically graded. The result promotes the effective utilization of A. mangium timber, which has a high annual growth rate, from managed forests, thus reducing the destruction of natural tropical forests.